Global Increase in Climate-Related Disasters - Vinod Thomas; Ramón López (Asian Development Bank (ADB), 2015)
Intense climate-related disasters - floods, storms, droughts, and heat waves - have been on the rise worldwide. At the same time and coupled with an increasing concentration of greenhouse gases in the atmosphere, temperatures, on average, have been rising, and are becoming more variable and more extreme. Rainfall has also been more variable and more extreme. Is there an ominous link between the global increase of these hydrometeorological and climatological events on the one side and anthropogenic climate change on the other? This paper considers three main disaster risk factors - rising population exposure, greater population vulnerability, and increasing climate-related hazards - behind the increased frequency of intense climate-related natural disasters. In a regression analysis within a model of disaster risk determination for 1971-2013, population exposure measured by population density and people's vulnerability measured by socioeconomic variables are positively linked to the frequency of these intense disasters. Importantly, the results show that precipitation deviations are positively related to hydrometeorological events, while temperature and precipitation deviations have a negative association with climatological events. Moreover, global climate change indicators show positive and highly significant effects. Along with the scientific association between greenhouse gases and the changes in the climate, the findings in this paper suggest a connection between the increasing number of natural disasters and man-made emissions of greenhouse gases in the atmosphere. The implication is that climate mitigation and climate adaptation should form part of actions for disaster risk reduction.
hdl:11540/5274
Keywords: C22; Q54; Q56; Q58; 330; climate; climate hazards; government policy; natural disasters; sustainable development